An Optimization Method for the Main Influence Factors on the Performance of Aerostatic Spindle - Dongju Chen; You Zhao; Ri Pan; Jinwei Fan (Shock and Vibration)
This paper proposes a novel optimization method to improve the performance of aerostatic spindle. The optimization process is based on the main factors affecting the load and stiffness of aerostatic spindle, which are determined by cross-correlation analysis. The maximum values of load capacity and stiffness are obtained from the relationship between the optimization function and the main influence factors. After optimization, the corresponding natural frequency has been improved, which indicates that the optimization method proposed in this paper is more efficient and reliable in the field of precision machining. The results will enforce the industrial application of aerostatic spindle system.